Acute Compressive Ulnar Neuropathy in a Patient of Dengue Fever: An Unusual Presentation - Anil K Mehtani; Ashutosh Jha; Himanshu Kataria; Vivek Jangira; Ajay Shukla (Journal of Orthopaedic Case Reports, 2013)
Introduction: Dengue haemorrhagic fever is known for its haemorrhagic and neurologic complications. Neurologic complications are caused by three mechanism namely neurotropism, systemic complications causing encephalopathy and postinfectious immune-mediated mechanisms. However acute compressive neuropathy due to haemorrhage is not frequent and we could find no literature describing this Case Report: We report a case of acute compressive ulnar neuropathy due to peri neural hematoma, following an attempt at intravenous cannulation in the cubital fossa in a patient of dengue haemorrhagic fever with thrombocytopenia. Immediate fasciotomy and removal of haematoma was performed to relieve the symptoms. Conclusion: Compression neuropathies can be seen in dengue hemorrhagic fever and removal of compressing hematoma relieves symptoms. Keywords: Dengue haemmorrhagic fever; coagulopathy; peri neural haematoma.